2018
DOI: 10.1002/gch2.201700090
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Heavy Metals from Battery Waste in Topsoil, Surface Water, and Garden Grown Maize at Omilende Area, Olodo, Nigeria

Abstract: Land pollution is a threat to sustainable agricultural development and food security in developing countries. Consumption of farm products from contaminated areas can generate health hazards to the diverse consumers along the food chain through the different pollutants in the products. This study is designed to determine the accumulation of Pb, Cd, and Fe in topsoil, surface water, and maize leaf, stem, grains, and root, cultivated in a garden nearby Ori‐Ile battery waste dumpsite, Omilende Area, Olodo, Nigeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 38 publications
(36 reference statements)
0
11
1
Order By: Relevance
“…Heavy metal contamination is a global issue [93][94][95][96][97] and of high significance in Nigeria. Evidence from research within the context of Nigeria suggests a growing concern for protecting different varieties of food from the toxic effects of heavy metals [30,69]. e present outcome from various laboratory investigations, such as those of Ogunkunle et al [56] and Obiora et al [29], show that some of these heavy metal contaminations, particularly those affecting dairies, most of the aquatic habitat, and the beverage industry, are within safety level, according to international standards.…”
Section: Arsenic (As)mentioning
confidence: 99%
“…Heavy metal contamination is a global issue [93][94][95][96][97] and of high significance in Nigeria. Evidence from research within the context of Nigeria suggests a growing concern for protecting different varieties of food from the toxic effects of heavy metals [30,69]. e present outcome from various laboratory investigations, such as those of Ogunkunle et al [56] and Obiora et al [29], show that some of these heavy metal contaminations, particularly those affecting dairies, most of the aquatic habitat, and the beverage industry, are within safety level, according to international standards.…”
Section: Arsenic (As)mentioning
confidence: 99%
“…TF reflects the concentration of metal in maize relative to that in the corresponding soil. A TF value higher than 1 indicates a high level of metal accumulation in the plant [39]. In this study, the TF values were far less than 1 for all six heavy metals, indicating low levels of metal accumulation in maize grains.…”
Section: Heavy Metal Levels In Maize Associated Soil and Irrigationmentioning
confidence: 47%
“…Former studies found that compared to other parts of maize, the grains have lower TF values [39,48], indicating low heavy metal uptake and accumulation in maize grains. The TF values of the six metals in this study followed the following sequence: Cd > Zn ≈ As > Cr > Cu > Pb.…”
Section: Heavy Metal Levels In Plant-soil-irrigation Systemmentioning
confidence: 99%
“…Similarly, in Ibadan (Oyo State), Pb and Cd concentrations detected in topsoil of battery waste dumpsite exceeded the environmental quality standards set by National Environmental Standards and Regulations Enforcement Agency (NESREA) for soils in Nigeria [28]. Street dumpsite soil samples in Osogbo, Osun state was also examined by [29] and the highest Lead concentration detected was 72.7 mg/kg.…”
Section: Heavy Metals Accumulation In Soilmentioning
confidence: 99%